Production of Single Cell Protein by Aspergillus niger Using a Mixture of Coffee Husk and Molasses as Substrate - Syahiddin Dahlan Said; Muhammad Zaki; Nasrullah - RCL; Mukhlishien Mukhlishien; Maulida Maulida; Meysa Nadia Harahap; Mentarina Rizki (Journal of Applied Technology, 2023)
Gayo is one of the districts in the province of Aceh, one of the largest Arabica coffee producers in Indonesia. So far, coffee husk produced from coffee fruit processing have not been used optimally, causing environmental problems. Efforts to utilize coffee husk as a substrate to produce single cell protein (SCP) can be considered, besides overcoming environmental problems, it will also produce alternative proteins to substitute traditional proteins. A study has been carried out to evaluate the potential of Gayo Arabica coffee husk as a substrate to produce SCP using solid state fermentation with Aspergillus niger as a bioconversion agent. The results showed that the C/N ratio and water content of the substrate were variables that greatly influenced protein production. The highest protein production was produced by substrate with a C/N ratio of 10 and a water content of 50% (w/w) with a fermentation time of 4 days. Increasing the level of molasses in the substrate mixture linearly increases protein production.Keywords: single cell protein, solid state fermentation, Aspergillus niger, coffee husk, molasses